2023
DOI: 10.52398/gjsd.2023.v3.i1.pp40-56
|View full text |Cite
|
Sign up to set email alerts
|

21st Century Skills development among young graduates

Abstract: This paper presents the results of the project “21st Century Skills: Changing the Approach to Teaching in Higher Education”, which was funded by the Erasmus+ programme between 2019 and 2021. The study involved seven institutions coming from different parts of Europe; mainly these were universities, but there was also one not-for-profit organisation, and one SME. Past and present-day initiatives and studies relating to the development of soft and digital skills among university students are investigated, with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Finally, the findings reiterate the importance of addressing students' skill development in higher education and specifically in graduate medical science programs through an explicit and intentional approach (Carpenter et al, 2022;Claydon et al, 2021;Crosta et al, 2023;Demaria et al, 2018;Gross & Sohl, 2021;Hart & McKinney, 2020;Jahn & Kenner, 2018;Pitan, 2017). The results also emphasize the importance of engaging students in reflective practise on their skill development (Carpenter et al, 2022;Minott, 2011).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Finally, the findings reiterate the importance of addressing students' skill development in higher education and specifically in graduate medical science programs through an explicit and intentional approach (Carpenter et al, 2022;Claydon et al, 2021;Crosta et al, 2023;Demaria et al, 2018;Gross & Sohl, 2021;Hart & McKinney, 2020;Jahn & Kenner, 2018;Pitan, 2017). The results also emphasize the importance of engaging students in reflective practise on their skill development (Carpenter et al, 2022;Minott, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…At the same time, the extent to which university graduates are equipped with 21st-century skills to enter the job market is questionable. For instance, Crosta et al (2023) highlight a mismatch between the actual value of these skills and the level of training provided by European universities to their students in this regard. Similarly, Grayson (2021) reports on low skill levels among university students and graduates in Ontario, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…As part of a European research project, through interviews and online surveys with labour market actors and academics in five countries (Bulgaria, the Czech Republic, Italy, Spain, and Turkey), Crosta et al (2023) found that the two most important employability skills were communication skills and collaboration with some differences between the countries However, with the help of questionnaires, they also identified the lack of competency-based assessment in tertiary education: 63% of the 156 higher education students from Bulgaria, the Czech Republic, Spain, and Turkey stated that they had never been evaluated using competencies as a framework (Crosta et al, 2023, p. 48). It was particularly salient in the qualitative summary of expert responses in Spain that "higher education tends to assess students based on content rather than competencies" (Crosta et al, 2023, p. 46) which is not an uncommon feature of programmes in HEIs in Europe.…”
Section: Research On Employability Skills -What Employers Demandmentioning
confidence: 99%
“…Apart from that, PE activities in schools can also be used to develop 21st century skills. The aspects of 21st century skills, such as critical thinking, teamwork and digital literacy have a significant positive impact on the career readiness of young graduates (Crosta & Bakay, 2023). Forms of 21st century skills include; Critical thinking, cooperation, com-munication and creativity are considered important in today's education.…”
Section: Introductionmentioning
confidence: 99%